2014
DOI: 10.1080/15348431.2014.944703
|View full text |Cite
|
Sign up to set email alerts
|

AbuelitaEpistemologies: Counteracting Subtractive Schools in American Education

Abstract: This autoethnographic inquiry examines the intersection of elder epistemology and subtractive education, exploring how one abuelita countered her granddaughter's divestment of Mexican-ness. I demonstrate how the grandmother used abuelita epistemologies to navigate this tension and resist the assimilative pressures felt by her granddaughter from school by consistently modeling, at home, a love for Mexican language and culture. I argue that grandmothers play a vital role in rooting young people to their linguist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…While the process of establishing shifts in the curriculum is one piece of a structural project related to content and pedagogy, another part of this has to deal with epistemologies. S. M. Gonzales’s (2015) work in this area uses personal narrative to examine the role of las abuelitas , or grandmothers, as educators in Mexican, Mexican American, and Chicana/o culture—paying careful attention to how grandmothers used abuelita epistemologies to counteract the subtractive schooling processes in the United States, in order to resist the assimilative pressures, and thus positively affect student adjustment and success.…”
Section: Disrupting Inequality Through Curriculum and Pedagogymentioning
confidence: 99%
“…While the process of establishing shifts in the curriculum is one piece of a structural project related to content and pedagogy, another part of this has to deal with epistemologies. S. M. Gonzales’s (2015) work in this area uses personal narrative to examine the role of las abuelitas , or grandmothers, as educators in Mexican, Mexican American, and Chicana/o culture—paying careful attention to how grandmothers used abuelita epistemologies to counteract the subtractive schooling processes in the United States, in order to resist the assimilative pressures, and thus positively affect student adjustment and success.…”
Section: Disrupting Inequality Through Curriculum and Pedagogymentioning
confidence: 99%
“…Their research found that kinship networks that included grandparents, aunts, uncles, and cousins were often undermined by a system designed to reinforce a nuclear family model that was limited in scope because it focused mostly on parents. Grandparents, who have status in many CLD systems and who help maintain family traditions while also helping children to re-shape themselves in new ways that compliment both their home and school culture, were often perceived by schools as a barrier that holds the family from moving forward into the contemporary (Gonzales, 2014;Leichter, 1974). …”
Section: Concluding Thoughts and Future Directionsmentioning
confidence: 99%
“…Early schooling in the Americas physically and mentally harmed the Aboriginal peoples of Canada, Native Americans, and Mesoamerican children and adolescents (Gonzales 2015;Kirmayer et al 2003;Quijada Cerecer 2013). Spanish missions, Indian boarding schools, and public schooling saw Indigenous ways of living as inferior.…”
Section: Intergenerational Trauma In the Classroom And The Loss Of Native Identitymentioning
confidence: 99%